Realitas Segregasi Gender di Pesantren - Evi Muafiah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
This research is motivated by a segregate learning model between men and women known as Single Sex Education (SSE). This model is regarded as one of the causes of lasting gender inequality, especially in pesantren. This research reveals; (1) the application of SSE, (2) the underlying reason and (3) its implications for the achievement of female students in pesantren in Ponorogo. This gender perspective qualitative research is the main data source is the words and actions of kiai, nyai, teachers and students selected by purposive sampling and snowballing. Data obtained through observation techniques, interviews, FGD and documentation are then analyzed by SSE theory. The result showed that (1) SSE is applied to the physical environment and student’s activities. In detail the segregation took place at a formal educational institution; MA, MTs and MD, organizational structure of foundations, boarding lodging, classroom learning, extra activities, and facilities. (2) The gender segregation is based on several reasons; religious, pragmatic, emergency, emancipatory and cultural. (3) It has positive implications for the existence of female students, because it has successfully increased the potential of female students from the academic, creative and independent aspects.